PARATE EXECUTIE AND PUBLIC POLICY. THE SUPREME COURT OF APPEAL PROVIDES FURTHER GUIDELINES - WG Schulze (Obiter, 2022)
The right of a creditor to realise the property of its debtor without first obtaining the permission of the court is clouded in controversy. This type of extra-judicial execution is known in Roman-Dutch law as parate executie (literally: “immediate execution”). The essence of parate executie is that it allows the creditor to self-help in the event of default by the debtor. The tenability of parate executie has come under judicial scrutiny in the recent past, not least because of its potential infringement of the provisions contained in section 34 of the Constitution of the Republic of South Africa, 1996. Section 34 provides that “[e]veryone has the right to have any dispute that can be resolved by the application of law decided in a fair public hearing before a court or, where appropriate, another independent and impartial tribunal or forum” (see in this regard, First National Bank of South Africa Ltd v Land and Agricultural Bank of South Africa; Sheard v Land and Agricultural Bank of South Africa 2000 3 SA 626 (CC); (2000 8 BCLR 876); Chief Lesapo v North West Agricultural Bank 2001 1 SA 409 (CC); Findevco (Pty) Ltd v Faceformat SA (Pty) Ltd 2001 1 SA 251 (E); De Beer v Keyser 2002 1 SA 827 (SCA); Senwes Ltd v Muller 2002 4 SA 134 (T); Shoprite Checkers (Pty) Ltd t/a OK Franchise Division v Juglal NO (unreported case no 6049/01, 13 Sep 2002 (D)) (which was endorsed on appeal in Juglal NO and another v Shoprite Checkers (Pty) Ltd t/a OK Franchise Division 2004 5 SA 248 (SCA)); Graf v Buechel 2003 4 SA 378 (SCA) (which dealt with a forfeiture clause (ie, pactum commissorium) and therefore falls outside the direct scope of the present note); and Bock v Dubororo Investments (Pty) Ltd 2004 2 SA 242 (SCA)). These cases have further been discussed in a number of case notes (see Scott “Summary Execution Clauses in Pledge and Perfecting Clauses in Notarial Bonds” 2002 65 THRHR 656 et seq; Steyn “Perfection Clauses, Summary Execution (Parate Executie) Clauses, Forfeiture Clauses (Pacta Commissoria) and Conditional Sales in Pledge Agreements and Notarial Bonds – The Position Clarified” 2004 Obiter 443 et seq; and Schulze “Parate Executie, Pacta Commissoria, Banks and Mortgage Bonds” 2004 37 De Jure 256 et seq). Although parate executie is employed by many creditors to realise the security that they hold, commercial banks, being the prime example of money lenders in modern times, have a particular vested interest in retaining parate executie as a valid instrument to realise movables that were given to the bank as security. In the recently reported decision in SA Bank of Athens Ltd v Van Zyl (2005 5 SA 93 (SCA)) the court was asked to pronounce on the validity of a clause that provides for parate executie on the movable property (in the present case: four investment policies) of a defaulting debtor which were held by a bank. The court was further asked to determine whether a parate executie clause is in conflict with public policy.